الرقابة الادارية و انعكاساتها على تحسين الأداء الوظيفي دراسة ميدانية بمتوسطات قصر الحيران الاغواط - شوشة خديجة; مايدي بشرى; معاش الطيب (My University, 2023)
Administrative control is of great importance within the organization because of its great impact on the performance of the individuals working in it, whether negatively or positively, and it is present in any institution. Therefore, our study aimed to identify the extent of the contribution of administrative control to improving job performance, as well as revealing a relationship between administrative control and job performance. And also knowing the role of administrative control in a successful evaluation of performance, and verifying the extent to which the applied control methods contribute to achieving the quality of job performance. Our study reached a number of results, the most important of which are: - Statistics indicate that workers work for a full 8 hours, and this is a positive thing as a matter of public responsibility. - The results showed that the criterion for evaluating performance is by observation during work by the official, as the worker accepts it and does not find embarrassment in it in terms of performing his duties. - Statistics indicate that workers, when they lack the raw materials that they use in their performance, perform their tasks with the materials they possess. - The results showed us that the inquiry on each absence was always - It appears that the largest percentage was for the answer in the form of yes, that the supervisory system as applied to every worker with the exception of this thing indicates the commitment of the official. Tags: control, performance, performance appraisal, performance appraisal